BCL6 repression of EP300 in human diffuse large B cell lymphoma cells provides a basis for rational combinatorial therapy - Cerchietti, Leandro C. (American Society for Clinical Investigation, 2010)

(untitled)
B cell lymphoma 6 (BCL6), which encodes a transcriptional repressor, is a critical oncogene in diffuse large B cell lymphomas (DLBCLs). Although a retro-inverted BCL6 peptide inhibitor (RI-BPI) was recently shown to potently kill DLBCL cells, the underlying mechanisms remain unclear. Here, we show that RI-BPI induces a particular gene expression signature in human DLBCL cell lines that included genes associated with the actions of histone deacetylase (HDAC) and Hsp90 inhibitors. BCL6 directly repressed the expression of p300 lysine acetyltransferase (EP300) and its cofactor HLA-B–associated transcript 3 (BAT3). RI-BPI induced expression of p300 and BAT3, resulting in acetylation of p300 targets including p53 and Hsp90. Induction of p300 and BAT3 was required for the antilymphoma effects of RI-BPI, since specific blockade of either protein rescued human DLBCL cell lines from the BCL6 inhibitor. Consistent with this, combination of RI-BPI with either an HDAC inhibitor (HDI) or an Hsp90 inhibitor potently suppressed or even eradicated established human DLBCL xenografts in mice. Furthermore, HDAC and Hsp90 inhibitors independently enhanced RI-BPI killing of primary human DLBCL cells in vitro. We also show that p300-inactivating mutations occur naturally in human DLBCL patients and may confer resistance to BCL6 inhibitors. Thus, BCL6 repression of EP300 provides a basis for rational targeted combinatorial therapy for patients with DLBCL.